7(x-6)=6x-69

Simple and best practice solution for 7(x-6)=6x-69 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-6)=6x-69 equation:



7(x-6)=6x-69
We move all terms to the left:
7(x-6)-(6x-69)=0
We multiply parentheses
7x-(6x-69)-42=0
We get rid of parentheses
7x-6x+69-42=0
We add all the numbers together, and all the variables
x+27=0
We move all terms containing x to the left, all other terms to the right
x=-27

You can always share this solution

See similar equations:

| 1-(+2)+2x=5(2x-5) | | 9x2-1800=0 | | 9x^2-1800=0 | | 3=5+-12x | | x1·x2= | | -18+5y=7y+20 | | 1+x/5=-4 | | -4s-16s+18=-14-12s | | -10.5n=-10.4n+1.67 | | 5.2a=3.64 | | -9=1/2x-5 | | 5x=10x-11 | | -20+13w=12w | | 15v-17=-16+13v-15 | | 360x=12 | | 5.7u+2.33+3.3u=8.1u-2.35 | | 256+16x=864 | | B=15.75-0.08x | | 8+6h=5h-6 | | -18+12m-17m=18-3m | | -14.9m+10.12=-14m+19.84 | | -8=-7+x/9 | | x+2/4=x+1/7 | | 13+19z=9+15z | | 7x-1=-3x=5 | | 3r=-8+5r | | 16-6c=-4c | | -20-9d-20=-3D+20 | | 7x/18=5/9+-8x/4 | | 7x-1=3xx=5 | | -17t-16=-16t+3 | | x+7/18=5/9+x-8/4 |

Equations solver categories